Morphological aspects determine the catalytic activity of porous hydrocalumites: the role of the sacrificial templates. (March 2022) - Muráth, S.; Varga, T.; Kukovecz, Á.; Kónya, Z.; Sipos, P.; Pálinkó, I.; Varga, G.
Abstract: Morphological modification of bulk layered double hydroxides (LDHs) into surface-engineered, porous materials enabled effective, base-catalyzed liquid phase Knoevenagel condensation in water. The increase in the number of the accessible basic sites on LDH engineering led to the enhancement of the reaction rate, whereas the significant changes in the relative strength of the basic sites were found to cause remarkable differences in the chemoselectivities. Thus, porous hydrocalumite (CaAl-LDH) catalysts allowed long-term and highly selective Knoevenagel condensation using reasonably mild reaction conditions. The advantages of heterogeneous nature and the recyclability of the hydrocalumites were also strengthened by advanced surface treatment. These key factors (basic sites, basic nature, and heterogeneity) can be fine-tuned by selecting the appropriate sacrificial template (cetyl trimethyl ammonium bromide, multiwalled carbon nanotubes, and Santa Barbara Amorphous-15), which regulates the morphology of the composites. Graphical abstract: Image 1 Highlights: Mesoporized hydrocalumites/hydrotalcites (LDHs) were designed and developed by a controlled morphological shaping. The quality of the sacrificial templates dictated the differences in the porosity of the desired products. In a Knoevenagel condensation, the catalytic behaviour of the LDHs were tuned by their surface functionality features.